ANALISIS DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM FARMASI DI BEI SEBELUM DAN SESUDAH PANDEMI COVID-19 - Dikdik Maulana (Accounting Research Journal, 2025)
Indonesia's pharmaceutical market faces the obstacle of a poor operating climate undermined by low levels of protection for intellectual property. In addition, the pricing and reimbursement system is underdeveloped. The pricing and reimbursement system reflects the underdeveloped status of the pharmaceutical market and requires restructuring and modernization. The target issues to be discussed are researched through research with specific themes and research topics by narrowing down the topic of discussion regarding Dividend Payout Ratio and Stock Price. The research method approach used is descriptive verification method, which is research that aims to determine the relationship between variables and other variables. This method is done by testing hypotheses and answering problem formulations through data collection. The data source used in this study is the official website of the Indonesia Stock Exchange (IDX). Based on the test results, the results of the research on the Dividend Payout Ratio variable state that there is an influence between Dividend Payout Ratios and stock prices, firm size has a significant effect on stock prices, dividend payout ratio has no significant effect on stock prices.